The Meanings of “Good Service Quality”: Insights from a Private University Brand in the Kingdom of Bahrain - Mahmood, Mahmood A. Husain; Mang'unyi, Eric E. (International Review of Management and Marketing, 2018)
The phenomenon of branding has become increasingly significant within the competitive tertiary education arena, particularly in emerging economies. Using ethnographic approach and supported by experiential and observation data collection techniques, the paper seeks to draw insights on service delivery quality of university customers' based on their experiences at a private university brand in the Kingdom of Bahrain. This study focuses on the conceptions and perceptions of service quality and brand meanings and their efficacy thereof among students and staff of a private university brand as a case of the research. The study reveals that students' service quality is associated with the benefit that they derive from this university brand – that is, attaining a degree certificate, which impacts on their satisfaction. It was also evident that the quality of lecturers' and availability of resources is seemingly of less importance. The study suggests a holistic approach that could be considered when developing a university brand. Keywords: Brand, private university, service quality. JEL Classifications: M30, M31, M37